Effectiveness of Booklet on Exclusive Breastfeeding in Improving the Knowledge and Attitudes of Mother Who Do Not Exclusively Breastfeed in the Work Area of Posyandu Sisir Batu City, East Java, Indonesia - Katmawanti, Septa; Eko Wardani, Hartati; Fauzi, Rosuzeita; Dewi Ningrom, Lia; Aflah, Dea (KnE Life Sciences, 2021)
In February 2019, the Sisir Health Centre in Batu reported that about 110 mothers in the area did not exclusively breastfeed. This behaviour of mothers was associated with their inadequate knowledge about and their attitude towards exclusive breastfeeding. The purpose of this research was to determine the effectiveness of a booklet on exclusive breastfeeding in improving the knowledge and the attitude of mothers who did not exclusively breastfeed in the working area of Sisir Health Centre, Batu. This research uses a pre-experimental design with a one group pre- and post-tests. A total of 53 samples were included in this study, selected through quota sampling. Knowledge and attitudes of mother were collected using questionnaire. Data were analysed using the Wilcoxon signed-rank test (nonparametric data analysis statistics) as the distribution was unnormal. The results showed that the Asymp. Sig Values (2-tailed) of both the mothers’ knowledge and their attitude were 0.000 or <0.05. Thus, it can be concluded that “Exclusive breastfeeding booklets are effective in improving maternal knowledge on and their attitude towards exclusive breastfeeding in mothers who do not exclusively breastfeed in the working area of Sisir Health Centre, Batu. Keywords: booklet, mother’s knowledge, exclusive breastfeeding, exclusive breastfeeding